2021
DOI: 10.21203/rs.3.rs-217660/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radiological Assessment of Response to Neoadjuvant Chemotherapy in Breast Cancer Females, Using Standard and Spectral Mammography

Abstract: Background Morphological assessment and measurement of the residual mass of the breast tumour following neoadjuvant chemotherapy (NACT) is the key to successful surgical treatment. The objective of our study was to evaluate the efficiency of contrast-enhanced spectral mammography (CESM) and conventional mammography (MMG) in detecting CR (complete response) following NACT, as well as to compare the efficiency of conventional mammography and contrast-enhanced spectral mammography is assessing the therapeutic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Consistent with previous studies we have shown that CESM has greater accuracy at predicting pCR than mammography. 10,[15][16][17][18] With respect to DBT, our results are similar to two studies which compared DBT to mammography and ultrasound, reporting a sensitivity of 44.7-50% and specificity of 91-97.6%. 11,19 However this is the first study to consider the combined use of CESM and DBT in the context of NACT.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous studies we have shown that CESM has greater accuracy at predicting pCR than mammography. 10,[15][16][17][18] With respect to DBT, our results are similar to two studies which compared DBT to mammography and ultrasound, reporting a sensitivity of 44.7-50% and specificity of 91-97.6%. 11,19 However this is the first study to consider the combined use of CESM and DBT in the context of NACT.…”
Section: Discussionsupporting
confidence: 88%